TEACHING VOCABULARY IN INDONESIAN EFL CLASSROOMS: A COMPARATIVE CASE STUDY OF JUNIOR HIGH SCHOOL STRATEGIES, CHALLENGES, AND STUDENT RESPONSES - Al Ikhsan Ihsan (GLOBAL: Education Language and Humanity Journal, 2025)
This study investigates the strategies used by junior high school English teachers in Yogyakarta, Indonesia, to teach vocabulary in English as a Foreign Language (EFL) classrooms. It also explores the pedagogical challenges they encounter and students’ responses to these instructional methods. Adopting a qualitative case study design, the research draws on classroom observations and semi-structured interviews with two teachers and six students from one public and one private school. The findings reveal a range of strategies, including mind mapping, translation tasks, mobile-assisted tools, and picture-based learning. However, their implementation varied, with student-centered and technology-enhanced methods leading to greater engagement and vocabulary retention. Key challenges included students’ difficulty memorizing words, low motivation, and disparities in digital proficiency between teachers and learners. The study highlights the importance of adaptive, context-sensitive pedagogy and suggests the need for greater institutional support for teacher training and technological integration. These findings offer practical implications for improving vocabulary instruction in similar EFL contexts.